PENGARUH KECEPATAN, KEAMANAN, DAN AKURASI TERHADAP KEPUASAN PELANGGAN SHOPEE DI KALANGAN GEN Z - Putri, Engyelita Verlianty; Marsella, Marsella; Halim, Calista Joice; Januardin, Januardin; Purba, Truly Okto Hasudungan (JURNAL LENTERA BISNIS, 2026)
Service providers are required by the sharp competition in the e-commerce sector to prioritize the pillars of security, speed, and accuracy as determinants of consumer satisfaction. This study is oriented to test and analyze the significance of the influence received by Shopee users on satisfaction in the Generation Z segment in Medan City from the dimensions of security, service speed, and accuracy.Quantitative research is the method implemented by this research, where primary data is the source of data collected in this study. Using a purposive sampling technique, with respondent criteria aligned with the research objectives, 100 selected respondents were recruited to complete a structured questionnaire. Multiple linear regression analysis was implemented to statistically process all data using IBM SPSS Statistics software. The research findings show that customer satisfaction is significantly influenced by security, speed, and accuracy, both partially and simultaneously. This suggests that shopee app user satisfaction can be increased by improvements in system security quality, service speed, and information accuracy in the transaction process.